Variables Factors in Wax Apple (Syzygium Samarangense) Wine Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Wax apple (S. samarangense) fruit is crispy, juicy and tasty with apple aroma. Fruit flesh contains spongy tissue. It represents potential benefits for human health because they are rich source of polyphenolic antioxidants. This fruit is also highly perishable. Its economic potentials have never been exploited. During its harvesting season, a considerable percentage of the fruits are not harvested due to lack of demand and inadequate storage facilities, therefore leading to wastage. The surplus could be used for fruit wine. Effect of primary fermentation duration (4, 6, 8, 10 days), sugar to pulp ratio (5, 10, 15, 20% w/w), Saccharomyces cerevisiae inoculation (2.0 x 106,4.0 x 106, 6.0 x 106, 8.0 x 106 cfu/g) on anthocyanin (mg/ 100 mL), total phenolic content (mg GAE/ 100 mL) and total ﬂavonoid (mg CE/ 100 mL) content of fermented wax apple fruit drink were thoroughly investigated. The secondary fermentation (1, 2, 3, 4 weeks) was also examined to improve the turbidity (mJ/cm2) and sensory score of the final fermented drink. The optimal conditions for fermentation of wax apple juice should be conducted at 8 days of primary fermentation with 15% of sugar supplementation inoculated with 6.0 x 106 cfu/ml of Saccharomyces cerevisiae and 4 weeks of secondary fermentation (aging) to get pleasant physico-chemical characteristics of fermented wax apple drink. Fermented Syzygium samarangense drink was red-pink, clear and transparent. This present study revealed that horticulture farmers would get more added values from wax apple fruits not only by local commerce but also processing. It could be processed by fermentation and conversion into high valued wineKeywords: Wax apple, Wine, Fermentation, Sacchromyces cerevisiae, Anthocyanin, Phenolic, flavonoid